Penerapan Model Brainstorming pada Materi Menulis Surat Resmi dalam Mata Kuliah Menulis Mahasiswa PBSI FKIP UPR Semester Genap 2018/2019 - Alifiah Nurachmana (JURNAL PENDIDIKAN, 2020)
The objectives of this study are: (1) to describe the process of applyingthe brainstorming model in learning to write official letters to students ofPBSI FKIP UPR Even Semester academic year 2018/2019, (2) describe theresults of applying the brainstorming learning model in writing officialletters to PBSI students Even Academic Year 2018/2019. The learningprocess of PBSI FKIP UPR students while participating in learning to writeofficial letters by applying a brainstorming model showed very good results,because all descriptors to assess the learning process were interpretedalmost entirely and in full. While the learning outcomes of PBSI FKIP UPRstudents in the activity of writing official letters by applying thisbrainstorming learning model has increased.